Transforming post-Catholic Ireland: religious practice in late modernity - Ganiel, Gladys (Oxford University Press, 2016)
'Transforming Post-Catholic Ireland' explores the dynamic religious landscape of contemporary Ireland, north and south, and to analyse the island's religious transition. It confirms that the Catholic Church's long-standing 'monopoly' has well and truly disintegrated, replaced by a mixed, post-Catholic religious 'market' featuring new and growing expressions of Protestantism, as well as other religions. It describes how people of faith are developing 'extra-institutional' expressions of religion, keeping their faith alive outside or in addition to the institutional Catholic Church. Drawing on island-wide surveys of clergy and laypeople, as well as more than 100 interviews, Gladys Ganiel describes how people of faith are engaging with key issues such as increased diversity, reconciliation to overcome the island's sectarian past, and ecumenism.